Electrospun Scaffold Micro-Architecture Induces an Activated Transcriptional Phenotype within Tendon Fibroblasts - Baldwin, Mathew J.; Mimpen, Jolet Y.; Cribbs, Adam P.; Stace, Edward; Philpott, Martin; Dakin, Stephanie G.; Carr, Andrew J.; Snelling, Sarah JB. (Frontiers in Bioengineering and Biotechnology, 2022)
Biomaterial augmentation of surgically repaired rotator cuff tendon tears aims to improve the high failure rates (∼40%) of traditional repairs. Biomaterials that can alter cellular phenotypes through the provision of microscale topographical cues are now under development. We aimed to systematically evaluate the effect of topographic architecture on the cellular phenotype of fibroblasts from healthy and diseased tendons. Electrospun polydioxanone scaffolds with fiber diameters ranging from 300 to 4000 nm, in either a highly aligned or random configuration, were produced. Healthy tendon fibroblasts cultured for 7 days on scaffolds with highly aligned fibers demonstrated a distinctive elongated morphology, whilst those cultured on randomly configured fibers demonstrated a flattened and spread morphology. The effect of scaffold micro-architecture on the transcriptome of both healthy and diseased tendon fibroblasts was assessed with bulk RNA-seq. Both healthy (n = 3) and diseased tendon cells (n = 3) demonstrated a similar transcriptional response to architectural variants. Gene set enrichment analysis revealed that large diameter (≥2000 nm) aligned scaffolds induced an upregulation of genes involved in cellular replication and a downregulation of genes defining inflammatory responses and cell adhesion. Similarly, PDPN and CD248, markers of inflammatory or “activated” fibroblasts, were downregulated during culture of both healthy and diseased fibroblasts on aligned scaffolds with large (≥2000 nm) fiber diameters. In conclusion scaffold architectures resembling that of disordered type III collagen, typically present during the earlier phases of wound healing, resulted in tendon fibroblast activation. Conversely, scaffolds mimicking aligned diameter collagen I fibrils, present during tissue remodelling, did not activate tendon derived fibroblasts. This has implications for the design of scaffolds used during rotator cuff repair augmentation.